LITERATURE STUDY ON ANTIHYPERTENSIVE THERAPY IN PREGNANCY - Junaedi; Nanang Kurnia Achmadi; Yetri Elisya; Dwi Yunita Rizki Fajarsari (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Hypertension is one of the leading causes of maternal and fetal mortality and has more serious repercussions during childbirth. The three foremost causes of maternal mortality in obstetrics are hemorrhages (45%), infection (15%), and preeclampsia (13%). In pregnancy, hypertension is referred to as systolic blood pressure above 140 mmHg or diastolic blood pressure higher over 90 mmHg. Due to the risk of teratogenic effects of medication and mother physiologic changes in response to pregnancy, treatment during pregnancy requires special consideration. Methyldopa and Nifedipine are antihypertensive medications that can be performed during pregnancy. Antihypertensive therapy in pregnancy should be determined based on the pregnant patient's age, the class of antihypertensive drugs, single medications, and antihypertensive therapy combinations. As stated by results of this study, more pregnant women had hypertension between the ages of 26 and 30. When compared to other antihypertensive groups, nifedipine plus calcium blockers (CCB) is the safest and most effective type of antihypertensive therapy for pregnant women. Furthermore, some patients with hypertension in pregnancy require a combination of therapies to meet blood pressure targets; the use of a combination of nifedipine and methyldopa has been shown to overcome hypertension in pregnancy.